2022
DOI: 10.1186/s12931-022-02181-9
|View full text |Cite
|
Sign up to set email alerts
|

A prediction model for hospital mortality in patients with severe community-acquired pneumonia and chronic obstructive pulmonary disease

Abstract: Background No personalized prediction model or standardized algorithm exists to identify those at high risk of death among severe community-acquired pneumonia (SCAP) patients with chronic obstructive pulmonary disease (COPD). The aim of this study was to investigate the risk factors and to develop a useful nomogram for prediction of mortality in those patients. Methods We performed a retrospective, observational, cohort study in the intensive care unit (ICU) of West Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…1 , 48 The influence of comorbidities on the prognoses of patients with AECOPD were inconsistent due to differences in the study population, comorbidities analyzed, and the relatively small sample sizes. 18 , 24 , 25 , 49 For example, Huang D et al found that in patients with AECOPD complicated with pneumonia (sample size: 873), diabetes and chronic kidney disease increased the risk of in-hospital mortality, while cardiovascular diseases did not. 49 Peng JC et al found that hypertension, diabetes, cardiovascular disease, chronic kidney disease, and malignancies did not significantly increase the 30-day risk of death in patients with AECOPD in the ICU (sample size: 494).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 , 48 The influence of comorbidities on the prognoses of patients with AECOPD were inconsistent due to differences in the study population, comorbidities analyzed, and the relatively small sample sizes. 18 , 24 , 25 , 49 For example, Huang D et al found that in patients with AECOPD complicated with pneumonia (sample size: 873), diabetes and chronic kidney disease increased the risk of in-hospital mortality, while cardiovascular diseases did not. 49 Peng JC et al found that hypertension, diabetes, cardiovascular disease, chronic kidney disease, and malignancies did not significantly increase the 30-day risk of death in patients with AECOPD in the ICU (sample size: 494).…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 24 , 25 , 49 For example, Huang D et al found that in patients with AECOPD complicated with pneumonia (sample size: 873), diabetes and chronic kidney disease increased the risk of in-hospital mortality, while cardiovascular diseases did not. 49 Peng JC et al found that hypertension, diabetes, cardiovascular disease, chronic kidney disease, and malignancies did not significantly increase the 30-day risk of death in patients with AECOPD in the ICU (sample size: 494). 24 In the present study, eight common and important comorbidities, including hypertension, ischemic heart disease, diabetes, cerebrovascular disease, bronchiectasis, interstitial lung disease, chronic hepatic insufficiency, and chronic kidney disease were analyzed ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al established a nomogram to assess the risks of hospital mortality among 611 patients who had both SCAP and chronic obstructive pulmonary disease (COPD). This nomogram included various factors such as chronic renal diseases, diabetes, systolic blood pressure, interleukin-6 (IL-6), fibrinogen, and BUN (AUC: 0.840, 95% CI: 0.809–0.872) ( 36 ). In a recent study by Song et al ( 37 ) a similar nomogram was developed to predict the 28-day mortality among elderly SCAP patients.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that after correcting for renal function, a high BUN concentration on admission was still closely related to the adverse outcomes of critically ill patients in the ICU [ 24 ]. In addition, the BUN-to-serum albumin ratio is an important prognostic factor for mortality and severity in patients with aspiration pneumonia, hospital-acquired pneumonia, and community-acquired pneumonia [ 25 , 26 ]. LDH is an enzyme present in the cytoplasm that is involved in lactate metabolism.…”
Section: Discussionmentioning
confidence: 99%